TRANSISI KURIKULUM DI INDONESI BERAKIBAT BAGI PELAYANAN BIMBINGAN DAN KONSELING DALAM PELAYANAN MAHASISWA DI UNIVERSITAS ISLAM NEGERI MAULANA MALIK IBRAHIM MALANG - TUTUT SUGIARTI (CENDEKIA: Jurnal Ilmu Pengetahuan, 2023)
This study aims to see and find out the effects of the transition from the 2013 curriculum to an independent curriculum in guidance and counseling services in the Faculties/Study Programs. This research was conducted using the Literature Review and Survey method, in which researchers reviewed various written articles, documents and files related to the Implementation of the 2013 Curriculum and the Independent Curriculum as well as unstructured interviews based on research topics regarding the Implementation of the 2013 Curriculum and the Independent Curriculum in Counseling Guidance services in the Faculty/Study Program. The results found that there are still problems experienced by counseling lecturers in the implementation of guidance and counseling services in the Study Programs in the 2013 Curriculum and the Independent Curriculum. The author is assigned as a Learning Technique Developer (PTP) at the Faculty of Psychology and has observed the implementation of the Independent Curriculum through student counseling guidance services, as a form of building the psychological well-being character of students with subject lecturers. In addition, collaborating with parents of students to participate in carrying out the role of guidance and counseling lecturers in building student character, because of the various positive impacts for guidance and counseling, through student character creation services, including improving and helping student achievement. Some students have difficulties in learning and understanding learning material, and require more attention from lecturers with personal guidance and counseling specifically for students, so that they can improve their academic achievement. ABSTRAKPenelitian ini bertujuan untuk melihat dan mengetahui akibat transisi kurikulum 2013 menjadi kurikum merdeka dalam pelayanan bimbingan dan konseling di Fakultas/Program Study. Penelitian ini dilakukan dengan metode Literature Review dan Survey, dimana peneli melakukan review terhadap berbagai tulisan artikel, dokumen, dan file yang terkait dengan Impelentasi Kurikulum 2013 dan Kurikulum Merdeka serta Wawancara tidak terstuktur berdasarkan topik penelitian mengenai Pelaksanan kurikulum 2013 dan Kurikulum Merdeka dalam layanan Bimbingan Konseling di Fakultas/Program Study. Hasilnya menemukan bahwa masih ada permasalahan yang dialami oleh Dosen BK dalam pelaksanaan layanan bimbingan dan konseling di Program Studi dalam Kurikulum 2013 maupun Kurikulum Merdeka. Penulis bertugas sebagai Pengembang Teknik Pembelajaran (PTP) pada Fakultas Psikologi telah mencermati adanya implementasi Kurikulum Merdeka melalui layanan bimbingan konseling mahasiswa, sebagai wujud pembinaan karakter kesejahteraan psikologi mahasiswa dengan dosen mata kuliah. Selain itu, berkolaborasi dengan orang tua mahasiswa agar ikut menjalankan peranan dosen bimbingan dan konseling dalam pembentukan karakter mahasiswa, sebab berbagai dampak positif untuk bimbingan dan konseling, melalui layanan wujud karakter mahasiswa, di antaranya meningkatkan dan membantu prestasi mahasiswanya. Beberapa mahasiswa ada kesulitan dalam belajar dan memahami materi pembelajaran, serta membutuhkan perhatian lebih dari dosen dengan adanya bimbingan dan konseling pribadi khusus mahasiswa, sehingga bisa meningkatkan prestasi perkuliahannya.